2008
DOI: 10.1088/1751-8113/41/43/435304
|View full text |Cite
|
Sign up to set email alerts
|

Dissipation and entanglement dynamics for two interacting qubits coupled to independent reservoirs

Abstract: Abstract.We derive the master equation of a system of two coupled qubits by taking into account their interaction with two independent bosonic baths. Important features of the dynamics are brought to light, such as the structure of the stationary state at general temperatures and the behaviour of the entanglement at zero temperature, showing the phenomena of sudden death and sudden birth as well as the presence of stationary entanglement for long times. The model here presented is quite versatile and can be of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(69 citation statements)
references
References 20 publications
3
63
2
Order By: Relevance
“…Besides confirming many features previously reported in the literature [21,22,23,24,25,26,27,28,29,30,31,32,33,34], our analysis showed that these terms produce long-time stationary entanglement [35,36,37]. The next natural task is thus to look for effects stemming from nonzero reservoir temperatures.…”
Section: Introductionsupporting
confidence: 87%
See 3 more Smart Citations
“…Besides confirming many features previously reported in the literature [21,22,23,24,25,26,27,28,29,30,31,32,33,34], our analysis showed that these terms produce long-time stationary entanglement [35,36,37]. The next natural task is thus to look for effects stemming from nonzero reservoir temperatures.…”
Section: Introductionsupporting
confidence: 87%
“…We have presented a general solution of a decay model for two interacting qubits, each one coupled to a different bosonic reservoir, previously solved in the zero-temperature only [35]. The analysis reported here clearly shows that the counter-rotating terms in the qubit-qubit interaction, usually neglected via a rotating wave approximation, cause two distinct physical effects, still observable at reasonable experimental temperatures (typically of the order of 10 ÷ 20 mK).…”
Section: Discussion and Concluding Remarksmentioning
confidence: 86%
See 2 more Smart Citations
“…Moreover in Ref. [24] the reservoirs are assumed to be independent, which is justified in the case of spatially separated Josephson qubits, since the noise in each device is due to impurities belonging to different parts of the whole superconducting circuit.…”
Section: The Physical System and The Microscopic Master Equationmentioning
confidence: 99%